Integrating sustainability into curricula: a systematic review of education for sustainable development - Wan Norsyafiqah Arinah Wan Nor Azmi,; Nur Husna Abd Wahid,; Sharifah Maryam Syed Azman,; Rozita Jayus, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Integrating sustainability into curricula is crucial for preparing students to address global environmental challenges. This systematic literature review, conducted using the PRISMA methodology, focuses on identifying effective pedagogical strategies for integrating sustainability into curricula and examines their impacts on students' learning outcomes. By analyzing 28 articles published between 2019 and 2024, the review highlights key pedagogical strategies such as problem-based learning, project-based learning, and service learning. These approaches are applied across various educational levels, including school, pre-university, and university settings. Additionally, it highlights the impacts of these integrations on students' learning outcomes, including the development of Education for Sustainable Development (ESD) competencies, fostering sustainability literacy, fostering global citizenship, and preparing students for sustainability-related careers. These findings provide valuable insights for educators and institutions aiming to effectively integrate sustainability into education, thereby equipping students with the necessary skills and knowledge to tackle global environmental challenges and contribute to a sustainable future.